Overview of Leptospirosis - Susi Setyawati, Kadek (Rifa'Institute, 2023)
Leptospirosis is one of the most important zoonoses worldwide and is a major public health problem in many countries. The disease is caused by spirochetes of the genus Leptospira and is transmitted through contact of abraded skin or mucous membranes with contaminated rodent urine, water, or soil. It is estimated that there are more than one million cases of severe leptospirosis per year worldwide. Leptospirosis can cause severe multiple organ failure with a mortality rate as high as 50%. Early recognition, diagnosis and treatment of leptospirosis can reduce morbidity and mortality. This overview will look out Leptospirosis thoroughly from the epidemiological burden, pathogenesis, clinical presentation and diagnosis, the current treatment and preventive leptospirosis